Psychoacoustic bias in vehicle interior noise – preliminary study - Aladdin, Mohd Farid; Abdul Jalil, Nawal Aswan (Elsevier, 2017)
This paper presents a preliminary study of psychoacoustic response bias in vehicle interior noise. The subjective response in psychoacoustics require human subject with relevant background and tendency for the best data analysis. In the vehicle interior sound quality subjective investigation, different vehicle owner have different expectation in vehicle comfort based on their preference. The perception and hearing sensitivity will be based on their day-to-day exposure. The objective of this paper is to study the bias response in vehicle sound quality judgement for different categories of car user (such as compact, sedan and luxury car). In this study, a survey has been conducted in an automotive service workshop. The questionnaire was designed to obtain the perception towards overall vehicle interior noise. The questionnaire are divided into three section; Part I: demographic information, Part II: Customer comfort level on level in vehicle cabin, Part III: Customer comfort level of sound loudness. The part III questions is created based on Loudness Fastl's Thermometer. The respondents were given brief demonstration of loudness and sharpness. Two examples of each type were given to assist respondent in grasping the concept and come out with their judgement toward the related sound mentioned in the survey. In this study, 30 male and 12 female respondents participated in the survey. The results showed80% of the respondents feel comfort with their respective vehicle regardless of what type of car there are driving. This indicates clear bias response based on the user's experience in driving different type of car. In a nutshell, different car owner define comfort level differently. Even if the sound level is different in comfort, sedan and luxury car, the driver still feel comfort which lead to different perception in defining vehicle cabin interior noise comfort.